Accumulation Pattern of Flavonoids during Fruit Development of Lonicera maackii Determined by Metabolomics - Zengxing Qi (MDPI AG, 2021)
Lonicera maackii (Caprifoliaceae) is a large, upright shrub with fruits that contain many bioactive compounds. Flavonoids are common active substances in L. maackii. However, there is a dearth of information about the accumulation of these flavonoids and their possible medicinal value. We used targeted metabolomics analysis based on ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) to analyze five developmental stages of L. maackii fruit. A total of 438 metabolites were identified in the five developmental stages, including 81 flavonoids and derivatives. The 81 flavonoids included 25 flavones and derivatives, 35 flavonols and derivatives, two isoflavones, three cyanidins and derivatives, eight procyanidins, and eight flavanones. In addition, we outlined the putative flavonoid biosynthesis pathway and screened their upstream metabolites. More importantly, we analyzed the accumulation patterns of several typical flavones and flavonols. The results reported here improved our understanding of the dynamic changes in flavonoids during fruit development and contributed to making full use of the medicinal value of L. maackii fruit.